Shoot Straight, You Bastards! Australians in the Boer War: the Breaker Morant Case - Martine Piquet (Cahiers Victoriens et Edouardiens)
Harry Harbord “Breaker” Morant (?1864–1902) was court-martialled and executed in February 1902 for killing prisoners during the Boer War. English-born, he had migrated to Australia in 1883 or 1884 and made a reputation for the two oddly juxtaposed aptitudes of taming wild horses (which earned him his nickname) and writing bush ballads. When the second Boer War of 1899–1902 broke out, he joined the South Australian Second Contingent and later joined the Bushveldt Carbineers in the rank of Lieutenant. His squadron was dispatched to the Spelongen region to counter the action of Boer commandos. Between July and September 1901 the detachment summarily executed a number of Boer prisoners, in accordance, they claimed, with Lord Kitchener’s orders “to make no prisoners”—which the British authorities denied were ever given. The fairness of the court-martial has since been disputed and, rightly or wrongly, Morant has become a folk hero in Australia, as a symbol of the reckless defiance of the underdog towards the authorities. This article tells the story of this singular episode of the Second Boer War and reflects on a few aspects of its perception in Australia.